Effects of resveratrol on bone metabolism and bone turnover related indexes in ovariectomized osteoporosis rats - Zhang, Yujin; Deng, Lin; Fan, Jiubo; Zhang, Yazhi (Cellular and Molecular Biology, 2020)
This study aimed to investigate the effects of resveratrol (RES) on bone metabolism and bone turnover related indexes in ovariectomized osteoporosis rats. 48 clean grade adult healthy unmated female SD rats were randomly divided into 6 groups, including normal control group (NCG), osteoporosis model group (OP MG), estrogen treatment group (17Î²-E2 group), RES low dose group (RES-L), RES medium-dose group (RES-M) and RES high dose group (RES-H). The rats in NCG and OP MG were given distilled water once a day and the rats in the other two groups were given 17Î²-E2 and resveratrol respectively. The levels of serum calcium (S-Ca), serum phosphorus (S-P), urinary calcium (U-Ca/Cr) and urinary phosphorus (U-P/Cr) were measured with an automatic biochemistry analyzer. The levels of serum osteocalcin (BGP), alkaline phosphatase (ALP), tartrate-resistant acid phosphatase (TRAP), type I amino front-end peptide (PINP), type I collagen strong carboxyl peptide (CTX-I), urine deoxypyridinoline (DPD) and serum estrogen were detected by enzyme-linked immunosorbent assay (ELISA). In the OP group, the serum estrogen levels, S-Ca and S-P decreased significantly and the expression of U-Ca/Cr and U-P/Cr increased significantly (P< 0.05). Compared with the OP group, the expression of S-Ca and S-P increased significantly and the expression of U-Ca/Cr and U-P/Cr decreased significantly (p< 0.05) after treatment. The levels of TRAP, BGP, DPD and CTX-I in the OP group increased significantly (P< 0.05). Compared with the OP group, the levels of TRAP decreased significantly (P< 0.05). The levels of PINP and ALP in OP MG increased significantly (P< 0.05). IP and ALP increased in the middle and lower levels (P< 0.05). The bone mineral density of the OP group decreased significantly (P< 0.05). Resveratrol can affect the changes in bone turnover in ovariectomized rats, promote bone formation in low estrogen state and inhibit bone resorption. Resveratrol may have a protective effect on the bone of ovariectomized rats.